2016
DOI: 10.1051/0004-6361/201526263
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cold cores

Abstract: Context. The association of filaments with protostellar objects has made these structures a priority target in star formation studies. However, little is known about the link between filament properties and their local environment. Aims. The datasets from the Herschel Galactic Cold cores key programme allow for a statistical study of filaments with a wide range of intrinsic and environmental characteristics. Characterisation of this sample can therefore be used to identify key physical parameters and quantify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 45 publications
(66 reference statements)
2
45
0
Order By: Relevance
“…This means that the fields typically contain a few Planck clumps but also a significant area of the surrounding cloud and even diffuse medium. This has enabled, for example, the study of the filamentary structure of the clouds around the clumps (Rivera-Ingraham et al 2016Malinen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the fields typically contain a few Planck clumps but also a significant area of the surrounding cloud and even diffuse medium. This has enabled, for example, the study of the filamentary structure of the clouds around the clumps (Rivera-Ingraham et al 2016Malinen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Rivera-Ingraham et al (2016) (Paper I hereafter), the data acquired by the Herschel Galactic Cold Cores Key Programme (GCC; P.I: M. Juvela et al 2012) was used to extract a sample of filaments for Galactic fields located at D ≤ 500 pc. This study complemented the work presented in Juvela et al (2012), and aimed to provide a robust characterisation of the physical properties of the filament population under different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies of filament widths in nearby clouds have generally confirmed this result when using submillimeter continuum data (e.g. Koch & Rosolowsky, 2015;Salji et al, 2015;Rivera-Ingraham et al, 2016), even if factor of ∼ 2-4 variations around the mean inner width of ∼ 0.1 pc have been found along the main axis of a given filament (e.g. Juvela et al, 2012;Ysard et al, 2013).…”
Section: Insights From Herschel and Planck: A Filamentary Paradigm Fomentioning
confidence: 83%